Essentials of filoviral load quantification. Issue 7 (July 2016) - Cnops, Lieselotte; van Griensven, Johan; Honko, Anna N; Bausch, Daniel G; Sprecher, Armand; Hill, Charles E; Colebunders, Robert; Johnson, Joshua C; Griffiths, Anthony; Palacios, Gustavo F; Kraft, Colleen S; Kobinger, Gary; et al.
Summary: Quantitative measurement of viral load is an important parameter in the management of filovirus disease outbreaks because viral load correlates with severity of disease, survival, and infectivity. During the ongoing Ebola virus disease outbreak in parts of Western Africa, most assays used in the detection of Ebola virus disease by more than 44 diagnostic laboratories yielded qualitative results. Regulatory hurdles involved in validating quantitative assays and the urgent need for a rapid Ebola virus disease diagnosis precluded development of validated quantitative assays during the outbreak. Because of sparse quantitative data obtained from these outbreaks, opportunities for study of correlations between patient outcome, changes in viral load during the course of an outbreak, disease course in asymptomatic individuals, and the potential for virus transmission between infected patients and contacts have been limited. We strongly urge the continued development of quantitative viral load assays to carefully evaluate these parameters in future outbreaks of filovirus disease.